Awareness of surgeons and surgical trainees of online web-based techniques for teaching laparoscopic surgery in north Queensland - Egedovo, Alfred; Ho, Yik-Hong; Larkins, Sarah; Mushuya, Chrispen; Ashraf, Muhammad; Nyandowe, Masimba; Emeto, Theophilus I.; Vangaveti, Venkat N. (International Surgery Journal, 2017)
Background: For generations, surgical training has followed the example of an apprenticeship model. However, many doctors see this training as insufficient and potentially unsafe for the patient. Web-based simulation training for teaching laparoscopic surgery is not only becoming increasingly popular but is cheaper in comparison to the traditional apprenticeship method. Objective is to assess the educational value of web-based training videos Methods: Data was obtained through questionnaires sent to consultant surgeons and surgical trainees at three sites in North Queensland. Study invited participants to complete a 24-item questionnaire on knowledge and attitudes. The questionnaires were distributed using online survey monkey software to send emails to the three Government Hospitals. Results: There was a response rate of 11.40%, Consultant surgeons (13/17; 72.20%) and surgical trainees (4/17; 22.20%). Majority of participant`s sources of learning laparoscopic surgery was from supervisors in operating theatre (64.30%) and online Web-based training video (WBTV; 7.10%), although satisfaction with current web-based training video resources was found to vary widely for a variety of reasons. WBTV were used mainly when required for clinical rotation. Conclusions: There was a response rate of 11.40%, Consultant surgeons (13/17; 72.20%) and surgical trainees (4/17; 22.20%). Majority of participant`s sources of learning laparoscopic surgery was from supervisors in operating theatre (64.30%) and online Web-based training video (WBTV; 7.10%), although satisfaction with current web-based training video resources was found to vary widely for a variety of reasons. WBTV were used mainly when required for clinical rotation.